Competency Improvement Through Promotion Creation Training with Canva for Prima UMKM Partners - Prastiyo Diatmono; Retno Sari Murtiningsih; Kristian Chandra (MSJ : Majority Science Journal, 2026)
Competency building in the Micro, Small, and Medium Enterprises (MSMEs) sector has become a key focus in national economic development, particularly amidst increasingly fierce competition and challenges faced by Mitra Prima MSMEs. With strong competencies, the capacity and skills of business members are expected to be able to adapt and innovate, thereby increasing their competitiveness and contribution to the local and national economy as a whole. In this context, promotional creation training using graphic design platforms such as Canva emerges as a highly relevant and strategic solution. The use of tools like Canva, known as a user-friendly graphic design platform, enables Mitra Prima MSME members to easily create attractive and professional promotional materials. This is crucial, considering that one of the main challenges faced by MSMEs is limited resources and capabilities to market products or services effectively. This training not only provides technical knowledge on how to use the platform but also provides insight into effective marketing principles, appropriate design selection, and how to convey messages that can attract consumer attention. This study aims to analyze in depth how this promotional creation training can significantly improve the competence of Mitra Prima MSME members in creating attractive and effective promotional materials. By applying quantitative and qualitative approaches, this study will not only measure the level of improvement in the technical skills of the participants but also explore its impact on the marketing results of MSMEs. Aspects to be analyzed include the level of brand recognition, sales increase, and consumer feedback on promotional materials produced after participating in the training. Through this study, it is hoped that information and data will be obtained that can serve as a basis for similar training programs in the future. In addition, the results of this study are also expected to provide recommendations to stakeholders, including the government, training institutions, and MSME development organizations, so that they can design and implement more effective development programs that are in accordance with the real needs of business members that can contribute to the development of the MSME sector as a whole and, more broadly, are expected to strengthen national economic growth